Effect of Human Resources on the Competitiveness of African Companies (Global Journal of Human-Social Science, 2025)
Annotation-The interest of the study is to make companies more competitive, especially those in developing countries, on an international scale. The main objective is to study the link between the human resources of companies and their competitiveness in international markets. Using SPSS software for data processing, we arrive at the following results: African companies employ much more women (99.2%) than men (98.1%) in their subsidiaries in international markets, the results show that exports of goods and services of companies represent 98.1% of the Gross Domestic Product (GDP) of African countries, exports of goods and services and primary income represent only 98.5% of the GDP of African countries.
Keywords: effect; human resources; companies; competitive; international markets